ANALISIS TINDAK INDISIPLINER SISWA SMP NEGERI - Putri, Nova Revita (Universitas Negeri Malang, 2018)
Abstract: The purpose of this research is done to know the student disciplinary action at every State Junior High School in Tempeh district. The type of this research is descriptive explorative with student disciplinary action variable. The results of this research are (1) the level of disciplinary action of junior high school students in Tempeh district is high, (2) the kinds of indiscipline acts that is when ditching the school students play with friends in the environment, while ditching the class, the students tend to be in the school canteen/cafeteria, incomplete uniform, while students are smoking at school parking, students are impolite to their schoolmates, students often criticize or mock, students play mobile phones during lessons, and students reply when there are others who disturb them that trigger on, and (3) the cause of the disciplinary action of the students of the State Junior High School in Tempeh subdistrict is an internal and external factor. Keywords: indiscipline's act, infringement, students, junior high school Abstrak: Tujuan penelitian ini untuk mengetahui tindak indisipliner siswa SMP Negeri di Kecamatan Tempeh. Jenis penelitian ini adalah deskriptif eksploratif dengan variabel tindak indisipliner siswa. Hasil penelitian ini yaitu (1) tingkat tindak indisipliner siswa SMP Negeri di kecamatan Tempeh tergolong tinggi, (2) macam-macam tindak indisipliner yaitu saat membolos sekolah siswa bermain dengan teman di lingkungannya, saat membolos kelas, siswa cenderung berada di kantin/ kafetaria sekolah, siswa berseragam tidak lengkap, saat bersekolah siswa merokok di parkiran luar sekolah, siswa berlaku tidak sopan kepada teman sekolahnya, siswa sering mencela atau mengejek, siswa bermain telepon genggam (handphone) saat pelajaran berlangsung, serta siswa membalas ketika ada orang lain yang mengganggunya yang memicu pada pembalasan dendam, dan (3) penyebab tindak indisipliner siswa SMP Negeri di Kecamatan Tempeh adalah faktor internal dan faktor eksternal. Kata Kunci: tindak indisipliner, pelanggaran, siswa, SMP Negeri DOI : 10.17977/um025v2i22018p122